Respuesta :
Answer:
A=h(b+c) solve for c
First, multiply h to b and c
A = hb + hc
Then, transfer hb to the other side and change its sign from positive to negative.
A – hb = hc
To get c, Divide both sides by h
(A – hb)/h = hc/h
(A - hb)/h = c OR c = (A – hb)/h
Example. Let us assume the following. A = 500 ; h= 10;b= 20; c= ?
c = (A – hb)/h
c = (500 – (10*20))/10
c = (500 – 200)/10
c = 300/10
c = 30
To check; use the original equation given.
A = h(b+c)
A = 10(20+30)
A = 200 + 300
A = 500. same as the figure given in the example.
[tex]\displaystyle\\Answer:\ b=\frac{A-hc}{h}[/tex]
Step-by-step explanation:
[tex]\displaystyle\\A=h(b+c)\\A=hb+hc\\A-hc=hb+hc-hc\\A-hc=hb\\Divide\ both\ parts\ of\ the\ equation\ by\ h(h\neq 0):\\\frac{A-hc}{h}=b\\ Hence,\\b=\frac{A-hc}{h}[/tex]